Colitis-induced oxidative damage of the colon and skeletal muscle is ameliorated by regular exercise in rats: the anxiolytic role of exercise - YEGEN, BERRAK; ERCAN, FERİHA; KASIMAY ÇAKIR, ÖZGÜR (WILEY, 2006)
Epidemiological studies have shown that exercise protects the gastrointestinal tract, reducing the risk of diverticulosis, gastrointestinal haemorrhage and inflammatory bowel disease, while many digestive complaints occurring during exercise are attributed to the adverse effects of exercise on the colon. In order to assess the effects of regular exercise on the pathogenesis of colitis, Sprague-Dawley rats of both sexes were either kept sedentary or given exercise on a running wheel (0.4 km h(-1), 30 min for 3 days week(-1)). At the end of 6 weeks, under anaesthesia, either saline or acetic acid (4%, 1 ml) was given intracolonically. Holeboard tests were performed for the evaluation of anxiety at 24 h before and 48 h after induction of colitis. Increased 'freezing time' in the colitis-induced sedentary group, representing increased anxiety, was reduced in the exercised colitis group (P < 0.05). On the third day following the colonic instillation, the rats were decapitated under brief ether anesthesia and the distal 8 cm of the colons were removed. In the sedentary colitis group, macroscopic and microscopic damage scores, malondialdehyde level and myeloperoxidase activity were increased when compared to the control group (P < 0.01-0.001), while exercise prior to colitis reduced all the measurements with respect to sedentary colitis group (P < 0.05-0.001). The results demonstrate that low-intensity, repetitive exercise protects against oxidative colonic injury, and that this appears to involve the anxiolytic effect of exercise, suggesting that exercise may have a therapeutic value in reducing stress-related exacerbation of colitis.
Keywords: INFLAMMATORY-BOWEL-DISEASE; PHYSICAL-ACTIVITY; OXYGEN METABOLITES; AEROBIC EXERCISE; FREE-RADICALS; STRESS; GLUTATHIONE; MECHANISMS; CAPACITY; PROTECTS